The polymorphism G894 T of endothelial nitric oxide synthase (eNOS) gene is associated with susceptibility to essential hypertension (EH) in Morocco - Sanaa Nassereddine; Hind Hassani Idrissi; Rachida Habbal; Rhizlane Abouelfath; Farah Korch; Majda Haraka; Adnane Karkar; Sellama Nadifi (BMC, 2018)
Abstract Background Hypertension is a multifactorial disease involving both environmental and genetic Factros. G894 T eNOS polymorphism has been suggested to be responsible for reduced NO synthesis, and EH development. The objective of our case-control study is to evaluate the potential association of G894 T eNOS polymorphism with Essential Hypertension (EH) susceptibility, among a sample of Moroccan patients. Methods One hundred forty five hypertensive patients were recruited from the department of Cardiology, University Hospital Center Ibn Rochd, Casablanca, Morocco, and compared to 184 apparently healthy subjects. DNA samples were genotype by PCR-RFLP method using MboI restriction enzyme. Results Our results showed a positive correlation between G894 T eNOS distribution and Alcohol and Obesity rik factors (P = 0.009 and 0.02 respectively). Patients with elevated Cardio Vascular Risk (CVR) carried out the higher frequency of homozygous mutant genotype TT (62.2%) and T mutant allele (77.8%), compared to median and low CVR groups. G894 T eNOS distribution was significantly associated to a high risk of EH occurrence under the GT and TT genotypes (OR [95% CI] = 20.2 [7.7-52.4], P <  0.0001; OR [95% CI] = 332.5 [98.2-1125.4], P <  0.0001 respectively), and the 3 genotypic transmission models (Dominant: OR [95% CI] = 43.2 [17.9-104.09], P <  0.0001; Recessive: OR [95% CI] = 47.7 [18.6-122.3]; P <  0.0001; Additive: OR [95% CI] = 14.02 [9.6-20.45], P <  0.0001). Conclusion Our study suggests a strong association of G894 T eNOS polymorphism with susceptibility to EH in Morocco. Studies trying to identify contributing genes may be very useful and allow recognizing the vulnerable individuals and classifying patients in subgroups with definite genetic and pathogenic mechanisms to achieve better prevention and therapeutics.